Dataset to submitted manuscript "Imaging the blinking properties of a mitochondrial fluorophore marker turns it into a multi-functional sensing probe" - Zhixue Du; Joachim Piguet; Glib Baryshnikov; Johan Tornmalm; Baris Demirbay; Hans Ågren; Jerker Widengren (Royal Institute of Technology, 2021)
This folder contains all raw data underlying the results presented in a manuscript, submitted to Light: Science & Applications, and entitled:

Imaging the blinking properties of a mitochondrial fluorophore marker turns it into a multi-functional sensing probe

Authored by:

Zhixue Dua, Joachim Pigueta,+, Gleb Baryshnikovb,+, Johan Tornmalma, Baris Demirbaya, Hans Ågrenb, Jerker Widengrena,*

a Royal Institute of Technology (KTH), Experimental Biomolecular Physics, Dept. Applied Physics, Albanova Univ Center 106 91 Stockholm, Sweden

b Royal Institute of Technology (KTH), Dept Theroretical Chemistry and Biology, Albanova Univ Center 106 91 Stockholm, Sweden

+ Contributed equally

* Corresponding author: Email:  jwideng@kth.se, Phone: +46-8-7907813

The data files are grouped into the different techniques used to generate them, and refer to the figures/tables in the manuscript where the extracted results are presented.

ABSTRACT

By transient state (TRAST) measurements, monitoring the average fluorescence intensity upon excitation modulation, we show that the mitochondrial localization fluorophore 10-Nonyl Acridine Orange (NAO) exhibits prominent singlet-triplet state transitions and can act as a light-induced Lewis acid forming a red-emissive doublet radical. The blinking properties resulting from these transitions can be monitored in a broadly applicable manner, and under biologically relevant conditions. By TRAST studies of NAO in small unilamellar vesicles (SUVs) we show that these blinking properties are highly environment sensitive, specifically reflecting local oxygen concentrations, redox conditions, membrane charge, fluidity and lipid compositions. In SUVs containing the phospholipid cardiolipin (CL) the NAO blinking properties depend not only on the concentration of the CL added, but also on the CL acyl chain composition. The blinking also reflects hydroxyl ion dependent transitions to and from the NAO doublet radical. This makes it possible to monitor local pH and buffering properties, from a 3D bulk buffer above the membrane, or from a 2D buffer at the membrane surface itself. Finally, by live cell TRAST imaging, we show that the fluorescence blinking properties of NAO can also be imaged in a spatially resolved manner, and that this commercially available location-specific fluorophore thereby can be turned into a multi-parametric intracellular sensing probe. This study demonstrates new possibilities for fundamental membrane studies in artificial vesicles and live cells, using existing fluorophore markers, monitoring parameters and conditions of large biological relevance, which are difficult to retrieve by other means.
Keywords: Fluorescence, NAO, mitochondria, blinking, redox, pH, imaging, photophysics, cell, membrane; Physical Sciences; Fysik